A distinct metabolic state arises during the emergence of 2‐cell‐like cells. (18th December 2019) - Rodriguez‐Terrones, Diego; Hartleben, Götz; Gaume, Xavier; Eid, André; Guthmann, Manuel; Iturbide, Ane; Torres‐Padilla, Maria‐Elena
Abstract: Pluripotent stem cells are thought of as a surrogate of early developmental stages that sustain the capacity to generate all cell types in the body, thereby constituting an invaluable tool to address the mechanisms underlying cellular plasticity. In the mouse, cells resembling totipotent 2‐cell‐stage embryos (2‐cell‐like cells) arise at a very low frequency in embryonic stem cell (ESC) cultures. However, the extent to which these early‐embryonic‐like cells recapitulate the molecular features of the early embryo is unclear. Here, we have undertaken a characterization of some of the metabolic features of early‐embryonic‐like cells in culture. Our data indicate that early‐embryonic‐like cells exhibit decreased glycolytic and respiratory activity, lower levels of reactive oxygen species and increased glucose uptake, suggesting a shift of the metabolic programme during 2‐cell‐like cell reprogramming. Accordingly, we find that 2‐cell‐like cells can be induced by defined metabolites. Thus, in addition to their transcriptional and chromatin features, 2‐cell‐like cells recapitulate some of the metabolic features of their in vivo counterpart. Altogether, our work underscores a distinct metabolic state of early‐embryonic‐like cells and identifies compounds that can induce their emergence in vitro . Synopsis: 2‐cell‐like cells share some metabolic features with the early mouse embryo, indicating a shift of the metabolic programme during 2‐cell‐like cell reprogramming. 2‐cell‐like cells exhibit decreased glycolytic and respiratory activity compared with ES cells. 2‐cell‐like cells do not upregulate oxygen consumption upon acute supplementation of pyruvate or of respiration‐uncoupling agents, suggesting diminished respiratory capacity. Metabolites such as sodium acetate, sodium l ‐lactate or d ‐ribose can induce the emergence of Zscan4 + and 2‐cell‐like cells in culture. Abstract : 2‐cell‐like cells share some metabolic features with the early mouse embryo, indicating a shift of the metabolic programme during 2‐cell‐like cell reprogramming.